Controle robusto da atitude de um nanossatélite - Camilo, Vitor Mendes (Universidade Federal de São Carlos, 2025)
Nanosatellites have been the subject of research and application in recent years due to the accessibility promoted by the standardization of components and structures. The various applications of this type of device require very specific and controlled behavior even in the presence of disturbances characteristic of low orbit, where such nanosatellites operate. Thus, this work proposes to implement a robust controller using the H-infinity method for nanosatellite attitude control. Furthermore, as a reference for performance and robustness comparison, it will be performed in parallel with a PID controller, which is the most conventional approach. Both controllers use reaction wheels as actuators. Specific adverse situations such as substantial attitude error and angular velocity, which are characteristic of the separation from the rocket, known as detumbling, are simulated, as well as the effect of different types of disturbances. To carry out the simulations, a platform provided by MATLAB/Simulink was applied and extended, adding the H-infinity and PID controllers and the reaction wheels. Finally, after performing the simulations in different scenarios, the results unanimously favored the H-infinity controller regarding energy consumption and tracking error.
Robust attitude control of a nanosatellite
Keywords: Nanossatélite; Controle de atitude; Controle robusto; Nanosatellite; Attitude control; Robust control; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS::CONTROLE DE PROCESSOS ELETRONICOS, RETROALIMENTACAO; ENGENHARIAS::ENGENHARIA AEROESPACIAL::SISTEMAS AEROESPACIAIS::SATELITES E OUTROS DISPOSITIVOS AEROESPACIAIS